A Framework to Promote ICT in K-12 Education in Developing Countries: A Case Study in Sudan - Tairab, Adam; Huang, Ronghuai; Chang, Ting-Wen; Zheng, Lanqin (Blended Learning: Aligning Theory with Practices, 2016)
Information and communication technology (ICT) plays an important role in improving education, specifically K-12 education in developing countries. Promoting ICT in education in Sudan as a developing country is one of the components of the national education policy. Sudan has launched many initiatives, aimed at implementing ICT in the education system. However, some factors hinder the development of ICT, including ICT policy, infrastructure, educational resources and teacher development, as well as curriculum and assessment. As a result, this study builds upon the global status of ICT to explore how ICT can be promoted in education, and how the experiences of other countries can support this study in formulating a framework to promote ICT in K-12 education in Sudan.